COVID-19 and slowdown of residents' activity: Feedback from a novel e-learning event and overview of the literature. Issue 4 (November 2021) - Calcagnile, Tommaso; Sighinolfi, Maria Chiara; Sarchi, Luca; Assumma, Simone; Filippi, Beatrice; Bonfante, Giulia; Cassani, Alessandra; Spandri, Valentina; Turri, Filippo; Puliatti, Stefano; Bozzini, Giorgio; Moschovas, Marcio; et al.
Objective: To evaluate the impact of an e-learning online event, created for supporting resident's training during the slowdown of surgical and clinical activities caused by COVID-19 pandemic. An overview of PubMed literature depicting the state of the art of urology residency in the COVID-19 era was performed as well, to contextualize the issue. Methods: An online learning event for residents was set up at the beginning of the pandemic; the faculty consisted of experts in urology who provided on-line lectures and videos on surgical anatomy, procedures, updates in guidelines, technology, training. The audience was composed of 30–500 attendees from Italy, USA, India and Belgium. A questionnaire to analyze relevance, satisfaction and popularity of the lessons was mailed to 30 local residents. Results and limitations: Almost all residents defined the web environment suitable to achieve the learning outcomes; the method, the number and the competence of the faculty were appropriate/excellent. Most of the younger residents (81.8%) stated their surgical knowledge would improve after the course; 72.7% declared they would take advantage into routine inpatients clinical activity. Nineteen more expert residents agreed that the course would improve their surgical knowledge and enhance their practical skills; almost all stated that the initiative would change their outpatients and inpatients practice. Overall, 44 articles available in PubMed have addressed the concern of urological learning and training during the pandemic from different standpoints; four of them considered residents' general perception towards web-based learning programs. Conclusions: The paper confirms residents' satisfaction with e-learning methods and, to our knowledge, is the first one focusing on a specific event promptly settled up at the beginning of the outbreak. Web-based educational experience developed during the pandemic may represent the very basis for the implementation of prospective on-site training and overall scientific update of future urologists.